2017
DOI: 10.1016/j.sjbs.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

A herbal formula, comprising Panax ginseng and bee-pollen, inhibits development of testosterone-induced benign prostatic hyperplasia in male Wistar rats

Abstract: A recent study reported that Panax ginseng (P. ginseng) has a protective effect on the development of benign prostatic hyperplasia (BPH). KH053 is used as a new herbal prescription consisting of P. ginseng and bee-pollen. The present study aimed to investigate whether the KH053 has inhibition effects on the development of benign prostatic hyperplasia (BPH) using an animal model with testosterone induced BPH. The experiment was carried out in forty male Wistar 7 week old rats that were divided into four groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…Subcutaneous injection of testosterone had no significant (p > .05) difference in weight gains in the untreated/treatment groups in comparison to the normal control (Table 2). A similar trend was observed by Park et al (2017) which reported a non-significant elevation in the body weight gain of experimentally induced BPH animals compared to the normal control. This could be attributed to the differences in the initial whole body weights and unknown physiological processes that may have occurred during prostate enlargement and the metabolism of administered substances.…”
Section: Bodyweight Gainsupporting
confidence: 85%
“…Subcutaneous injection of testosterone had no significant (p > .05) difference in weight gains in the untreated/treatment groups in comparison to the normal control (Table 2). A similar trend was observed by Park et al (2017) which reported a non-significant elevation in the body weight gain of experimentally induced BPH animals compared to the normal control. This could be attributed to the differences in the initial whole body weights and unknown physiological processes that may have occurred during prostate enlargement and the metabolism of administered substances.…”
Section: Bodyweight Gainsupporting
confidence: 85%
“…Generic bee pollen composition data were considered sufficient for most purposes, but now the usefulness of bee pollen-specific composition data is increasingly being acknowledged [8,9]. Recent research has also shown that bee pollen possesses therapeutic benefits for improving the cardiovascular system, stimulating body immunity [10], promoting antitumor effects, delaying aging [11], scavenging free radicals, regulating intestinal function [12], and treating prostate disease [13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study showed that the Panax ginseng CAMAYER ( P. ginseng ) protected development of prostate in the rats (Kim et al, 2014, Kim et al, 2015a, Kim et al, 2015b, Park et al, 2017a, Park et al, 2017b). However, PMC, vlPAG, and MPA regions in the brain have not been investigated.…”
Section: Introductionmentioning
confidence: 99%